Supporting identification of neonatal conjugated jaundice. (24th May 2012) - See, L; Gordon, M; Mukherjee, A
Abstract : Case presentation: We present a case of a 36 week old baby born in poor condition requiring intubation at 2 hours of life and required at least> 8 ml/hr of intravenous dextrose infusion to optimise blood glucose levels. Along with congenital hyperinsulinism and other complications of prematurity. he developed a conjugated jaundice.. Whilst there was a daily enquiry as to the colour of the baby's stools, these were reported normal by several staff members. 8 days later, there was a biochemical cholestatic picture, despite still being asymptomatic. One of the authors reviewed the stools, which were pale cream / grey in colour and thought to be suspect. On further questioning, his stools had appeared this way for 10 days. He was investigated extensively and after an episode of sepsis, transferred to the regional Liver unit, where he was diagnosed with billary sludging. He is now doing well and has been discharged. Discussion: Whilst it did not have a major impact on the outcomes in this case, there was clearly a problem with the subjective interpretation of suspect stools. This was amongst a variety of professionals, including junior medical and neonatal nursing staff. Within the hospital environment this may be less important to identify, but within the community setting, recognition of suspect stools is a key screening tool. Previous reports in neonates in the context of bilious vomiting has previously identified variations in the subjective interpretation of samples and suggested the utility of objective vomitus colour charts1 . Our experience in this case suggests that a similar problem may exist with regards recognition of suspect stools and a similar resource for objective identification should be used. The Children's liver foundation has produced such materials to support frontline workers (figure 1 ), which is available in a variety of forms. Conclusions: Within a neonatal intensive care environment, there was lack of recognition of stools that were suspect of a cholestatic jaundice. In line with previous research in neonates, we would suggest the utility of objective resources to standardise the identification process with the aim of supporting high quality screening both inside and outside of hospital.